Geospatial Data Analysis of School Distribution in Baghdad City - Alatta, Hassan J.; George, Loay E.; Behadili, Suhad Faisal; Sayyid, Baqer H.; Ali, Maryam Hussain (Iraqi Journal of Science, 2023)
Education and lifelong learning are necessary components of daily city life for urban communities to encourage sustainable and positive communities. The study attempts to analyze the actual school distribution patterns and densities in Baghdad, the Iraqi capital. The significance of this study is that it is associated with one of the essential aspects of humanity: the improvement and affluence of schooling; it impacts school attendance limitations and educational evolution. The education process has been inextricably tied to students’ timely and orderly entrance to their schools. Hence the decision maker and planner are concerned by this. The statistics examined elementary and high schools, and the investigated data are related to the Ministry of Education that was available in 2004. Regarding spatial analysis and results assessment, this work employs Microsoft Excel techniques, ArcGIS, C# simulator, and the buffer methodology. It has depicted the school densities and assessed the distances between them using spatial analytic techniques. The study reveals that the school distribution is uneven, and there is a disparity among neighbors in the spatial distribution. Also, the in-between distances of observed schools formulate four significant patterns. At the same time, this study offers important information about the spatial distribution of schools as a significant influencing indicator. In the future, it will be beneficial to investigate the student’s geographical accessibility to their residence and the transportation to/from these schools.